On the Issue of Origin of the Yakut Epic Olonkho - Vasiliy Nikolayevich Ivanov; Antonina Fedorovna Koriakina; Gulnara Egorovna Savvinova; Ruslan Nikolayevich Anisimov (Journal of History Culture and Art Research, 2018)
The issue on the origin of the Yakut heroic epic Olonkho was covered in works in history and ethnography of the Yakuts back in the 19th century, for instance, in the famous monograph Yakuts. Experience of ethnographic research by a Polish exile V.L. Seroshevskiy (1896). Since that time, this issue was interesting for many, but no special monograph research has been done yet. Currently, the issue of Olonkho origin is gaining special scientific and general cultural significance, as on November 25, 2005 the Yakut heroic epic Olonkho according to the historical decision of UNESCO was granted the high status “Masterpiece of oral and non-material heritage of humanity”. The Yakut epic is a part of the multicomponent epic creative work of the Turkic nations but it was the only one to get such a high international recognition. This paper aims to revive the scientific interest to the issue of the Yakut epic’s genesis. To date, some rich source-related and historiographical material has been accumulated for broader generalizations – the main point is that the Yakut epic is becoming an important object of comparative historical analysis of the origin of all Turkic epics. The thing is that epic researchers admit that almost a thousand years of existence isolated from the whole Turkic world in the North-East of Asia kept many archaic features of the epics of the ancient ancestors – natives of Central Asia and Southern Siberia. It became clear that Olonkho origin is organically linked with the ethnic history of its nation.The paper follows this comprehensive process reflected in works by archeologists, ethnographers, historians and linguists. Their latest achievements are impressive, bringing a lot of novelty into the conventional views of origins and development of the Yakut epic. The paper attempts to specify that novelty and rationalize the idea that time has come to introduce that novelty into science to solve the long-standing issue of origin of the Yakut heroic epic Olonkho.